2021
DOI: 10.1002/jcsm.12755
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impact of sarcopenia in solid cancers treated with immune checkpoint inhibitors: a meta‐analysis

Abstract: Sarcopenia, which is characterized by a decrease in muscle quantity or quality, is commonly observed in patients with cancer. Recent research has reported contradictory results on the association between sarcopenia and the efficacy of immune checkpoint inhibitors (ICIs). We conducted a systematic review and meta-analysis to investigate this discrepancy. We systematically searched three electronic databases to identify articles reporting on the association between sarcopenia and treatment outcomes in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 62 publications
(517 reference statements)
3
52
0
Order By: Relevance
“…[44][45][46] The items in the scoring systems include sites of metastases, serum LDH level, serum albumin level, performance status, age, and NLR. The addition of other predictive markers, such as tumor mutational burden 5 and sarcopenia, 47 may further increase the predictive ability. Recent reports showed that post-treatment NLR is indicative of progressive F I G U R E 4 Forest plots of studies evaluating odds ratios for the neutrophil-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] The items in the scoring systems include sites of metastases, serum LDH level, serum albumin level, performance status, age, and NLR. The addition of other predictive markers, such as tumor mutational burden 5 and sarcopenia, 47 may further increase the predictive ability. Recent reports showed that post-treatment NLR is indicative of progressive F I G U R E 4 Forest plots of studies evaluating odds ratios for the neutrophil-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly used indices for sarcopenia include PMI and skeletal muscle density (SMD). Both indices have been shown to be associated with the prognosis of several types of cancer [46]. However, only a few reports investigate their significance in HNC [23,31].…”
Section: Plos Onementioning
confidence: 99%
“…Sarcopenia is characterized by the progressive and systemic loss of skeletal muscle mass and strength, leading to adverse outcomes, such as reduced quality of life and mortality [5]. There have been reports that sarcopenia affects the prognosis of various malignancies [26][27][28]. We have also reported that sarcopenia is a poor prognostic factor in patients with unresectable esophageal cancer [7] and that sarcopenic obesity is a poor prognostic factor in patients with resectable esophageal cancer [29].…”
Section: Discussionmentioning
confidence: 99%